Casas dramatúrgicas: material criativo para ensino de dramaturgia - Adélia Aparecida da Silva Carvalho (2021)
In this work, I propose the construction of a creative material for the teaching of dramaturgy aimed, especially, for theater students (undergraduate, technical, artistic-professional courses), based on a reflection on my training process as a dramatist, student and teacher, in an autobiographical journey through the houses I lived in the cities of Mariana, Ouro Preto, Belo Horizonte and Macapá. I take as a reference for this research the phenomenology from Bachelard, developed through self-writing procedures, from the perspective of the darkening of this thought, based on the idea of writing proposed by Conceição Evaristo, recognizing as production of knowledge the writing itself, as woman/black/dramatist who investigates the protagonism of experiences that emerge from memory, in a movement of recovery and valorization of ancestry subjected to erasure and silencing throughout history. The proposed material is built from the elaboration of letters, in a reference to Paulo Freire's pedagogical letters, to provoke the exercise of dramaturgical writing beyond the rules established by traditional drama.